Technology-Based Intervention for Depression in Adolescence: A Literature Review - Syulthoni, Zain Budi; Karimah, Azimatul; Nastiti, Aria Aulia (Journal of Medicine and Health Technology, 2025)
Depressive disorder is a disorder which frequently found in adolescence. Although some interventions had already known, many adolescence had difficulty to access care when needed, and adherence to therapy. We aimed to introduce using technology-based interventions for depression in adolescence. We searched PubMed, Springer, Sage, and Science Direct for articles in English using the search terms “adolescent depression” and “depression”, combined with additional search terms, “technology-based” “online” “computer-based” “computerized” “prevention” “treatment” “CBT” “videoconference”. We focused on papers from past 5 years, but also included papers published in the past 10 years (if sparse). We found 25 articles were suitable for this topic. This review resulted some novel development intervention such as Self-Monitoring and mood assessment, Computerized Cognitive Behaviour Therapy, and videoconference therapy that had benefit could increase the coverage of the patient, adhered more to the therapy, more convenient to access from wherever they live, and cost the least for the patient than conventional therapy that showed the same effectiveness. Technological development in medical care, specifically in mental health, was a possible solution to increase the coverage of intervention for depression in adolescence. Further research is needed on the effectiveness of this technology-based intervention in larger population.